Impact of work demand constraints on psychological distress through workplace bullying and personality traits: A moderated-mediation model - Naseem, Khalida; Ali, Majid (Frontiers in Psychology, 2023)
Purpose: This study addresses human aspects of sustainable development in organizations and main focus of the study is to investigate the negative aspects of workplace bullying on humans mentle health. This study investigated how workplace work constraints play a role in increasing psychological distressdecreasing through the mediating role of workplace bullying.This study also considers personality traits that play a role in preventing psychological distress resulting from workplace bullying. Design/methodology/approach: The authors collected data by means of a self-administered questionnaire, distributed among 1000 employees, randomly selected, patronized among three service sectors, namely the health sector, Education sector, and Forest department in the city of Lahore in Pakistan. The data was analyzed by employing structural equation modeling (SEM) using Smart PLS 3.3.3. Findings: Results of this study reveal that work demand constraints (WDC) play a significant role in workplace bullying and have an impact on increasing psychological distress. Personality traits play a moderating role between work demand constraints and workplace bullying behavior on the one hand and psychological distress on the other hand; however, openness to experiences was found to have a moderating relationship between work demand constraints and bullying behavior. Meanwhile, agreeableness and openness to experiences were found to have a moderating relationship between WDC and psychological distress. Practical implications: This study also has practical implications such as providing psychological counseling, personality development training etc. Originality: The relationship of work demand constraints with psychological distress and workplace bullying through direct and indirect moderating effects of personality traits in Pakistan's service sector are unique contributions of this study.